(untitled) (Journal of the College of Basic Education, 2022)
The purpose of this study was to investigate the relationship between gender, level of education, being relative or a non-relative of Psychiatric patient and type of Psychiatric diagnosis ( psychotic vs neurotic), on the Attitudes Towards Mental Illness. To achieve the purpose of this study, the attitude scale toward mental illness ( ASTMI) , developed by Cohen and strong ( 1962), and modified to the Arab culture by Bou-Median (1989) was administered to 730 individuals of both relatives and non-relatives of mentally ill persons. The results revealed that there was a slight positive attitude towards mental illness among Jordanians , and no relationship between gender and attitudes towards mental illness. It revealed however, that there was a significant difference ( = 0.05 ) among different levels of education, on favor of moderate and high – educated individuals on four of the five dimensions of the ASTMI scales ( psychotherapy) , social restrictiveness’, humanistic view and social interaction. The sample of the study consisted of all female students in Mutah basic school (N=64) which was randomly chosen. The sample was divided into two equivalent groups: experimental and control group. The T. test and some statistical procedures ( e.g, mean and standard deviation) were employed to answer the question of the study. The finding of the study indicated that were no significant differences between the effectiveness of the unit teaching method and traditional method on both variables: students achievement and their learning retention. In view of these findings, several recommendations were made. On the whole, it was recommended that teachers should use different teaching methods, particularly, unit teaching method by which they can develop student’s abilities and skills.